THE VALIDITY AND FEASIBILITY OF A HANDBOOK ON THE PROPERTIES OF LIGHT AND REFLECTIONS INTEGRATED WITH 1-SIDE HOLOGRAM LEARNING MEDIA FOR MIDDLE SCHOOL STUDENTS - Dwita Nahru Faradisa; Agung Mulyo Setiawan (SPEKTRA: Jurnal Kajian Pendidikan Sains, 2025)
Based on the needs analysis conducted by the researcher, we found that 71% of students had difficulty with the properties of light and reflection material, and 75% of students preferred innovative books integrated with learning media over conventional books that were often used by teachers. Therefore, it is necessary to develop a handbook on the properties of light and reflection, which is integrated with 1-side hologram media. The purpose of this study was to develop and analyze the level of validity and feasibility of this handbook. The method used to develop the handbook is the ADDIE model (Analysis, Design, Develop, Implement, and Evaluate). To obtain the validity and feasibility, the instruments were developed and distributed to expert validators, teachers, and students. We succeeded develop the handbook and it was declared valid with a percentage of 81.5% and 95.2% from the material and media aspects. This product was also declared feasible with a percentage of 81.4% and 92.9% according to students and teachers. Therefore, these results indicate that the handbook on the properties of light and reflection integrated with 1-side hologram media has been declared valid and feasible to use in middle school students.